Disabilities and Disparities in Oral Health-Related Quality of Life: A Systematic Review and Meta-Analysis in Saudi Arabia - Faris Yahya I. Asiri; Marc Tennant; Estie Kruger (Medicina)
Background and Objectives: In Saudi Arabia, persons with disabilities (PWDs) face considerable oral health challenges, including a higher prevalence of dental caries and gingival inflammation, which adversely affects their oral health-related quality of life (OHRQoL). This population experiences distinct and substantial barriers in accessing adequate dental care. This systematic review and meta-analysis aims to quantify disparities in OHRQoL between PWDs and individuals without disabilities in Saudi Arabia, focusing on caries and gingivitis prevalence, and to identify specific areas for intervention. Materials and Methods: A structured search of PubMed, Scopus, Web of Science, and Google Scholar yielded 803 articles, of which seven met the inclusion criteria. These studies reported on OHRQoL and oral health outcomes in populations with autism, Down syndrome, cerebral palsy, and hearing impairments. Data on caries rates, gingival health, and self- or caregiver-reported quality of life were extracted and analysed. Results: PWDs in Saudi Arabia exhibit significantly higher caries prevalence (ranging from 60% to over 80%) and moderate-to-severe gingival inflammation (up to 60%) compared to individuals without disabilities. The caregivers of children with disabilities reported heightened stress levels, and PWDs experienced reduced functional and social well-being. These disparities were compounded by limited preventive care access and high unmet treatment needs, particularly among those with severe disabilities and limited caregiver support. Conclusions: PWDs in Saudi Arabia face marked oral health disparities, with notably higher rates of dental caries and gingivitis, severely impacting their quality of life. The findings underscore the need for targeted oral health policies and community-based interventions to enhance care accessibility, promote preventive measures, and address the unique needs of this vulnerable population.